2020
DOI: 10.2196/19891
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Ethical Concerns in Implementing Enhanced Surveillance Methods to Improve Continuity of HIV Care: Qualitative Expert Stakeholder Study

Abstract: Background Retention in HIV care is critical to maintaining viral suppression and preventing further transmission, yet less than 50% of people living with HIV in the United States are engaged in care. All US states have a funding mandate to implement Data-to-Care (D2C) programs, which use surveillance data (eg, laboratory, Medicaid billing) to identify out-of-care HIV-positive persons and relink them to treatment. Objective The purpose of this qualitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The improved HIV treatment outcomes observed among people living with HIV who received supportive services from Rainbow Family were likely a major contributing factor to the higher cumulative survival in the exposure group. Decades of research have shown that retention in care and ART adherence are essential to achieving and maintaining viral suppression, improving immune function, and thereby reducing ARM among people living with HIV [ 37 - 42 ]. Our results suggest that the observed reductions in all-cause mortality between the exposure and control groups were primarily driven by reductions in ARM as NARM did not significantly differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The improved HIV treatment outcomes observed among people living with HIV who received supportive services from Rainbow Family were likely a major contributing factor to the higher cumulative survival in the exposure group. Decades of research have shown that retention in care and ART adherence are essential to achieving and maintaining viral suppression, improving immune function, and thereby reducing ARM among people living with HIV [ 37 - 42 ]. Our results suggest that the observed reductions in all-cause mortality between the exposure and control groups were primarily driven by reductions in ARM as NARM did not significantly differ between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our qualitative interviews have been reported and discussed elsewhere [10][11][12], but we briefly summarize here. Expert stakeholder interviewees included 30 participants from North Carolina; the remainder lived in other US states (n = 15) or outside the United States (n = 2).…”
Section: Qualitative Stakeholder Interviewsmentioning
confidence: 99%
“…The workshop design was informed by a set of qualitative interviews conducted in 2018-2019 with 47 expert stakeholders and 18 recently incarcerated PLWH. These qualitative interviews examined the public health benefits, ethical challenges, and practical opportunities in using publicly available jail records, court records, and state health department HIV registry records to improve the continuity of care for PLWH experiencing incarceration [10][11][12]. In this report, we review this background interview study and the discussion of its results by the stakeholders from the field who participated in the 2020 workshop.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…A collaborative D2C model may be initiated by health departments with primary healthcare providers, or vice versa , by using HIV case surveillance data and other data sources [ 8 , 10 ]. The literature shows some success in implementing D2C and improving HIV care outcomes [ 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%